Assessing the Integration of Genomic Medicine in Genetic Counseling Training Programs. Issue 4 (8th January 2014) - Profato, Jessica; Gordon, Erynn S.; Dixon, Shannan; Kwan, Andrea
Abstract: Medical genetics has entered a period of transition from genetics to genomics. Genetic counselors (GCs) may take on roles in the clinical implementation of genomics. This study explores the perspectives of program directors (PDs) on including genomic medicine in GC training programs, as well as the status of this integration. Study methods included an online survey, an optional one‐on‐one telephone interview, and an optional curricula content analysis. The majority of respondents (15/16) reported that it is important to include genomic medicine in program curricula. Most topics of genomic medicine are either "currently taught" or "under development" in all participating programs. Interview data from five PDs and one faculty member supported the survey data. Integrating genomics in training programs is challenging, and it is essential to develop genomics resources for curricula.